Numerical investigation of multiphase supersonic swirl flow inside convergent-divergent nozzle. (June 2016) - Eslamian, Ehsan; Shirvani, Hassan
Numerical study of multiphase swirl flow induced by helical insert inside the supersonic nozzle is investigated as applied in sandblasting systems. The finding of this research is crucial in improving the performance of abrasive blasting systems by reducing operation time and saving energy. Simulations are performed with Reynolds Stress Model turbulence modelling to capture anisotropy inside the flow. To simulate particles inside the nozzle, discrete phase model has been applied. The multiphase Eulerian method did not provide accurate results on modelling particles with small volume fraction ( < 10%), and also it was not capable of modelling particles interaction. The analyses are performed at three inlet pressures (2, 3 and 4 atm) with constant mass flow rate for particles. The results show that swirl effect increases the mixing feature of the flow, and therefore increases the cleaning area on a working surface. Furthermore, with swirl there was less reduction in maximum velocity compare with single phase simulations, hence particles will have greater speed at the exit of the nozzle.